Analisis Porositas dan Permeabilitas Batupasir Sebagai Potensi Reservoir Airtanah Daerah Tudi dan Sekitarnya - Irmawati Irmawati; Aang Panji Permana; Ahmad Zainuri (-, 2026)
Sandstone is a mixture or collection of rock fragments and mineral grains resulting from the natural erosion of various rock types. Changes and the presence of mineral grains in sandstone are strongly controlled by sedimentation processes during deposition, such as weathering in the source area, increasing distance and transport from the source area to the sedimentation environment, and diagenesis. This study aims to analyze the potential of sandstone in the Tudi area and its surroundings as a groundwater reservoir based on porosity and permeability analysis. This study used field geological mapping, porosity analysis, and permeability analysis. The sandstone units in the study area have varying porosities and permeabilities. Sample 15 BP has poor porosity, while sample 2 BP has good porosity. However, both samples have high permeability, indicating rapid water flow through them. The potential of sandstone in the study area as a reservoir rock in both samples is very good, as rapid fluid flow can accelerate the extraction or utilization process.